Novel dibenzothiophene chromophores with peripheral barbituric acceptors - Sperátová, Michaela; Jedyrka, Jaroslaw; Pytela, Oldřich; Kityk, Iwan V.; Reshak, Ali H.; Bureš, Filip; Klikar, Milan (Elsevier, 2019)
A series of novel chromophores based on central 2,8-disubstituted dibenzothiophene (DBT) or dibenzothiophene-S,S-dioxide (DBTO) has been designed and prepared. The interconnection of DBT(O) central scaffold with two peripheral barbituric acceptors via various π-spacer allowed significant property tuning of target chromophores. Four new final chromophores and six DBT(O)-intermediates have been successfully synthesized and fully characterized. Experimental and calculated data showed that the fundamental properties are affected by the chromophore A-π-D-π-A or A-π-A-π-A arrangement (DBT vs. DBTO) and the π-linker (ethenylene vs. ethynylene). Thorough structure-property relationships have been elucidated and discussed in detail. © 2019 Elsevier Ltd